Controlling banana bunchy top virus outbreak in east Africa - Mahuku, George; Kumar, P. Lava (International Institute of Tropical Agriculture, 2022)
Bananas (and plantain, Musa spp.) are the most important crops contributing to food security and the income of millions of smallholder farmers in East Africa. Banana bunchy top virus (BBTV, genus Babuvirus), an aphid-transmitted virus first reported in 2021 in Tanzania and Uganda, is wrecking banana production in several regions and threatening to spread further in East Africa. The BBTV has no effective solutions. Preventing the virus establishment is the best strategy. The remedial procedure of eradicating infected mats and replanting with clean planting materials is laborious and not favored by the smallholders because of its laborious nature and high cost. IITA and national program partners in Tanzania and Uganda, as part of the Plant Health Initiative, has initiative efforts to control and prevent the further spread of the BBTV outbreak in East Africa. It involve surveys to determine the extent of BBTV spread, implement eradication actions, and provide virus-free planting materials to recover banana production. Additionally, increasing awareness about the new threat and mitigation actions, strengthen NARS's capacity for surveillance, diagnostics, eradication, and production of clean planting material, and establish a regional ALLIANCE to coordinate monitoring, early detection, and take needed action.